Empowerment and Literacy Initiatives to Enhance Ultra Micro Debtor Classes: Strategies for Sustainable Regional Economic Growth - Kurniawati, Atika Detty; Febrianti, Putri; Suryani, Suryani; Rizky, Ilham; Dewi, Nurma Gupita (Jurnal Akuntansi dan Bisnis, 2024)
This article explores empowerment and literacy initiatives aimed at enhancing the capacity of ultra-micro debtor classes as a strategy for fostering sustainable regional economic growth. The study focuses on developing entrepreneurial competencies, financial literacy, and access to relevant technologies for ultra-micro debtors, who often face challenges such as limited education, financial knowledge, and access to resources. Through case studies in regions with significant ultra-micro economic activity, the research identifies community-based empowerment methods, financial literacy training, and digital platforms to support small business management. The findings reveal that these programs not only improve the productivity and income of debtors but also strengthen local economic resilience, promote financial inclusion, and create new job opportunities. The article concludes that collaboration between local governments, financial institutions, and local communities is crucial to ensuring the sustainability of these programs in supporting regional economic growth.Keywords: Ultra-micro debtors, empowerment initiatives, financial literacy, entrepreneurial development.